The Effect of Perioperative Music Listening on Patient Satisfaction, Anxiety, and Depression: A Quasiexperimental Study. (7th February 2020) - Tan, Daryl Jian An; Polascik, Breanna A.; Kee, Hwei Min; Hui Lee, Amanda Chia; Sultana, Rehena; Kwan, Melanie; Raghunathan, Karthik; Belden, Charles M.; Sng, Ban Leong
Abstract : Background . The effect of perioperative music listening has been proven to relieve preoperative anxiety and depression, while improving patient satisfaction. However, music listening has not been extensively studied in Singapore. Therefore, the primary aim of our study is to investigate the patient satisfaction towards perioperative music listening in the local setting. The secondary aim is to investigate the effect of perioperative music listening in reducing patient surgery-related anxiety and depression. Methods . After obtaining ethics board approval, we conducted a quasiexperimental study on a cohort of female patients who were undergoing elective minor gynaecological surgeries. Apple iPod Touch™ devices containing playlists of selected music genres and noise-cancelling earphones were given to patients to listen during the preoperative and postoperative periods. Hospital Anxiety and Depression Scale (HADS), EQ-5D-3L questionnaire, music listening preferences, and patient satisfaction surveys were administered. Wilcoxon signed-rank and McNemar's tests for paired data were used for analysis. Results . 83 patients were analysed with 97.6% of patients in the preoperative period and 98.8% of patients in the postoperative period were satisfied with music listening. The median (IQR [range]) score for preintervention HADS anxiety was 7.0 (6.0 [0–17]), significantly higher than that in postintervention at 2.0 (4.0 [0–12]) (P < 0.001 ). Similarly, there was a significant reduction in preintervention HADS depression as compared to postintervention (P < 0.001 ). These results were corroborated by similar findings from the EQ-5D-3L questionnaire. Conclusion . Perioperative music listening improved patient satisfaction and can reduce patient anxiety and depression. We hope to further investigate on how wider implementation of perioperative music listening could improve patient care.